A new stegelytrine leafhopper genus from China and Thailand (Hemiptera: Cicadellidae) - Zhang, Yalin; Wei, Cong; Webb, M. D. (Zootaxa, 2006)
A new Oriental stegelytrine leafhopper genus, Wyuchiva, and two new species, Wyuchiva elegantula (type species) from Thailand and Wyuchiva menglaensis from China, are described and illustrated. The taxonomic position of the new genus is discussed and phylogenetic remarks on this and a related genus, Temburocera Webb, 1999, are given.